A fine structure physical map of the short arm of chromosome 5. - Overhauser, J (1986)
A series of somatic cell hybrids that retain abnormal chromosomes 5 from 11 different persons with deletions or translocations involving 5p have been isolated. One hundred twenty DNA fragments isolated from a genomic library enriched for sequences from 5p were regionally localized by Southern blot analysis of the hybrid cell deletion mapping panel, including five DNA fragments that reveal restriction fragment length polymorphisms. The fine structure physical map of 5p together with the identification of additional polymorphic loci will facilitate the construction of a complete linkage map of this region. In addition, DNA fragments localized to a region near the 5p15.2-5p15.3 border, which appears to be the segment of 5p that is critical in producing the phenotype associated with the cri du chat syndrome when it is rendered hemizygous by deletion, will be useful in a molecular and DNA level analysis of this deletion syndrome.